2020
DOI: 10.1101/2020.12.04.20244145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatigue outcomes following coronavirus or influenza virus infection: A systematic review and meta-analysis

Abstract: ObjectivesFatigue is a pervasive clinical symptom for many infected with respiratory viruses such as influenza or coronaviruses. Prior evidence from influenza and coronavirus epidemics suggest that fatigue symptomology may continue beyond the acute phase, lasting for several months to several years post-discharge. This systematic review aimed to examine long-term fatigue prevalence among survivors and among communities, as well as investigate the current evidence for associated factors.DesignSystematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This forms the basis for considering the development of awareness programs for society regarding the safety profile of available vaccines, as well as the significant advantages of vaccination [ 28 ]. One of the most commonly reported mild adverse events was fatigue, which was also observed by the authors of other studies [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 75%
“…This forms the basis for considering the development of awareness programs for society regarding the safety profile of available vaccines, as well as the significant advantages of vaccination [ 28 ]. One of the most commonly reported mild adverse events was fatigue, which was also observed by the authors of other studies [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 75%
“…88 Fatigue is common after infection with other coronaviruses and influenza, with 1 study reporting 41% of participants experiencing fatigue after recovery from severe acute respiratory syndrome (SARS), Middle East respiratory syndrome, and influenza, in addition to SARS-CoV2. 89 In other studies, participants have reported symptoms of fatigue, myalgia, and psychiatric impairments for as long as 4 years after acute infection with Middle East respiratory syndrome and SARS. 28,[90][91][92] Six studies with available data assessed PASC symptoms of fatigue, among other symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the acute phase of COVID-19 usually lasts two to four weeks, during which the virus is actively shed and the onset of post-acute sequelae is usually considered after week 5 [16]. IAV is usually cleared within 5-6 days in adults and post-acute symptoms may include chronic fatigue that has been reported up to six weeks post the initial infection [17]. Schematic overview of symptoms, virus load and inflammation levels in the pre-acute, acute and post-acute phase of a (non-persistent) viral infection.…”
Section: What Are Post-acute Sequelae Of Viral Infections?mentioning
confidence: 99%